Analysis Factor of Capital Structure Property and Real Estate Companies in Indonesia - Ranila Suciati; Unggul Purwohedi; Gatot Nazir Ahmad (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
This study aims to determine the effect of company Size (SIZE), Liquidity(LIQ), Growth Opportunity (GROWTH), Tangibility (TANG), dan Bussines Risk (RISK) of Capital Structure-property and real estate in Indonesia. This research is quantitative research aiming to work out a systematically explain the facts and properties in an object in the study then do the merger between related variables in it with the presentation of secondary data from the financial statements of banking companies in the country of Indonesia. The population used in this study is a banking company listed in Indonesia stock exchanges in the period 2009-2016. Research results for property and real estate in Indonesia The value of R square model is 0,589 percent means that the variation of capital structure that can be explained by the independent variables in the analysis of Size, Liq, Growth, Tang, and Risk of 58.90 percent of the remaining of 41.1 percent explained by other factors not included in this study.